Mining-Induced Damage Characteristics of Floors during Fully Mechanized Caving Mining: A Case Study - Yulong Jiang; Dongfeng Zhang; Kai Wang; Xiaoqiang Zhang (Advances in Materials Science and Engineering)
To study the mining-induced damage characteristics of floors during fully mechanized mining, in situ measurements were performed using the hollow inclusion strain sensors in the No. 100502 (80 m, 180 m) mining face of the Yitang Coal Mine in the Huoxi coal field in the Shanxi Province of China. The in situ measurement results show that the failure depths of the floor rocks in the 100502 (80 m) and 100502 (180 m) mining faces were 12.50∼14.65 m and 17.50∼19.20 m, respectively. The longer the mining face was, the greater the failure depth and the more severe the deformation and damage of the floor rocks were. The failures of the damaged floor rocks can be divided into two types: pull-pressure strain mutations and abnormal mutations. With the advancement of the mining face, the strain increments of floor rocks at different buried depths showed obvious advanced and lagged responses. Specifically, the advanced response distance decreased with a negative exponential trend, while the lagged response distance generally first increased and then decreased as the depth increased. The results can not only provide important guidance to coal mining under water pressure, but also offer a key theoretical reference for failure depth control of floor rocks under similar geophysical conditions.